2008
DOI: 10.1007/s11845-008-0140-4
|View full text |Cite
|
Sign up to set email alerts
|

Portal hypertension and hypersplenism in a patient with a Bochdalek hernia: a case report

Abstract: Congenital diaphragmatic hernias may present in the adult. Their presentation is variable, and they may produce life-threatening complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…CT scan of her abdomen diagnosed Bochdalek hernia, and strangulation of the spleen in the left hemithorax. This resulted in left‐sided portal hypertension, hypersplenism, and thrombocytopenia 12 …”
Section: Discussionmentioning
confidence: 99%
“…CT scan of her abdomen diagnosed Bochdalek hernia, and strangulation of the spleen in the left hemithorax. This resulted in left‐sided portal hypertension, hypersplenism, and thrombocytopenia 12 …”
Section: Discussionmentioning
confidence: 99%
“…25,26 So far, about 100 cases of BH in adults have been reported in the literature, but the exact prevalence is unknown. [9][10][11][12][13][14][15][16] In the studies on the corpse, its prevalence was reported 0.014-0.05%. 4,6 The main symptom of BH in adults is chronic abdominal pain, but it can cause obstruction, strangulation, and rupture of the viscera, requiring urgent intervention.…”
Section: Discussionmentioning
confidence: 99%
“…So far, about 100 cases of BH in adults have been reported in the literature, but the exact prevalence is unknown. [9][10][11][12][13][14][15][16] Here we wish to report a case of large BH with displacement of the kidney, spleen and part of the small intestine and colon into the left hemi-thorax in a 50-year-old man.…”
Section: Introductionmentioning
confidence: 99%
“… 11 A similar clinical scenario whereby a patient underwent splenectomy to decompress sinistral portal hypertension has been reported. 6 Splenectomy provided sufficient space to suture the defect in the diaphragm, but we could have attempted splenopexy because hypersplenism might be relieved after CDH repair. Clinical evidence on splenectomy for hypersplenism in such a complicated situation is lacking.…”
Section: Discussionmentioning
confidence: 99%
“… 3 5 Because of volvulus or incarceration, herniated abdominal organs can suffer from hemodynamic disorders such as hypersplenism or even avascular necrosis. 6 Here, we describe a 10-year-old male patient who presented with asymptomatic CDH along with hypersplenism. All descriptions and discussions of this case did not involve human subjects research, thus no ethical approval was required.…”
Section: Introductionmentioning
confidence: 95%